Exploring craft practice in learning communities - Møller, Trine; Riis, Kirstine (FormAkademisk, 2021)
This paper presents an initial research project to explore what characterizes knowledge production in craft practice situated in an informal/neutral learning arena outside the education institution. The research project is carried out by craft and design researchers from Norway and Denmark. The project participants include students, academics, older generation volunteers with craft experience, freelance designers, and arts and craft persons, as well as researchers. The overall methodology is a case study approach and has references to practice-led research, participatory design research and A/R/Tography. In this paper we present the research design of the project. Along a theoretical framework consisting of research perspectives of each of our institutional traditions, we lastly discuss the challenges in engaging a neutral learning arena, throughout and as preparation for our research project.